High-strength galvanized and galvanized annealed steel sheet and manufacturing method
Patent Information
- Application Number
- KR1020257003545
- Authority / Receiving Office
- KR · KR
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2023-03-14
- Filing Date
- 2024-03-14
- Publication Date
- 2026-10-13
- Estimated Expiration
- 2044-03-14
Smart Images

Figure 112025012409939-PCT00014_ABST
Abstract
Description
Technology Field
[0001] This application claims priority to U.S. provisional patent application serial number 63 / 451,994, filed on March 14, 2023, titled “High Strength Galvanized and Galvannealed Steel Sheets and Manufacturing Method,” the disclosure of which is incorporated herein by reference. Background Technology
[0002] There is a demand for high-strength and high-ductility steel in automotive applications. The use of high-strength steel materials has led to weight reduction and improved impact safety in vehicles. At least in the steel market for automotive applications, new steels aim to meet the demand for high maximum tensile strength, excellent ductility, improved strain hardening behavior, and formability, while also possessing the capability for galvanizing (GI) and galvanizing (GA).
[0003] Several groups of steel offering varying strength levels have been proposed and used in the automotive and other markets. One example is dual-phase (DP) steel, composed of a ferrite phase and an integrated martensitic phase such as a filament. DP steel offers excellent ductility and formability with relatively low yield strength (YS) and maximum tensile strength (UTS). In other words, the final tensile strength is generally less than 600 MPa. Another example of steel is multi-phase (MP) steel, composed of a ferrite phase, a bainite phase, and a martensitic phase. MP steel has higher yield strength and maximum tensile strength compared to DP steel. In other words, the maximum tensile strength is generally in the range of 700 to 1000 MPa. Another example is composite-phase (CP) steel, containing a ferrite-bainite phase, a martensitic phase, and retained austenite and / or pearlite. CP steel has higher strength compared to DP and MP steels. In other words, the maximum tensile strength is generally in the range of 980 to 1200 MPa. There are also single-phase (SP) steels that have a microstructure with bainite or martensite and provide very high yield strength and maximum tensile strength. That is, the maximum tensile strength is in the range of 1300 to 1700 MPa, but the ductility and formability are relatively low compared to DP, MP, and CP steels.
[0004] By way of example only, U.S. Patent Publication US2013 / 008570 relates to high-strength steel having a maximum tensile strength of 1100 MPa, formability, strength-elongation balance, and bendability. The microstructure described in US2013 / 008570 consists of more than 50% martensite, more than 15% ferrite-bainite, and 0 to 5% polygonal ferrite. This disclosure does not disclose the galvanizing-galvanealing performance of the steel.
[0005] International patent publication WO2012 / 153016 relates to cold-rolled steel having a maximum tensile strength of more than 1000 MPa and an elongation of more than 12%. The microstructure described in WO2012 / 153016 consists of 5 to 15% martensite, 10 to 15% retained austenite, and 5 to 20% polygonal ferrite. This publication does not disclose the galvanizing-galvannealing performance of the steel.
[0006] U.S. Patent 11,047,020 relates to cold-rolled and hot-dipped steel having a maximum tensile strength of 980 to 1180 MPa. The described steel microstructure consists of 50 to 90% martensite, 5 to 50% ferrite, and bainite. U.S. Patent 11,047,020 discloses steel with galvanizing-galvanealing performance, but the maximum tensile strength is 1180 MPa.
[0007] U.S. Patent 8,840,834 relates to ultra-high strength steel having a maximum tensile strength of 1400 MPa or more. The microstructure consists of more than 80% auto-tempering martensite with precipitated iron-based carbides, less than 5% ferrite, less than 10% bainite, and less than 5% retained austenite. However, the steel of Patent '834 will exhibit a loss of galvanized annealing (GA) performance due to the low percentage of magnetic phases, such as ferrite, presented at high galvanized annealing (GA) temperatures. Furthermore, as the magnetic phase increases, the tensile strength of the steel of Patent '834 will decrease at the expense of a higher percentage of auto-tempering martensite.
[0008] Japanese Patent JP2528387 relates to ultra-high strength cold-rolled steel having a maximum tensile strength of at least 1500 MPa and good formability by performing annealing under specific conditions, rapid cooling with spray water, and overaging treatment. The steel of this Japanese patent would not be suitable for galvanizing because the galvanizing temperature is much higher than the overaging temperature used.
[0009] International Patent Publication WO2021 / 176249 relates to ultra-high strength cold-rolled and galvanized steel sheets having a tensile strength of 1450 MPa or higher. The steel microstructure consists of 80 to 90% martensite and the remainder being ferrite and bainite, containing 5% or more ferrite and / or 5% or more bainite. Intercritical annealing (IA) between Ac1 and Ac3 temperatures was used to obtain 5 to 15% ferrite for GA performance. However, the steel described in WO2021 / 176249 provides a very narrow IA processing window, making it difficult to control the ferrite ratio. When the IA temperature was low, GA performance was present, but the maximum tensile strength was lower than 1450 MPa. When the IA temperature was high, the maximum tensile strength was higher than 1450 MPa, but GA performance was lost. This disclosure did not explain the effect of the IA processing window on the balance between tensile strength and GA performance. means of solving the problem
[0010] Currently, there are various types of steel, some of which are described above, but there is a continuing need for improved galvanizing-galvanizing annealing steel products with a wider GI / GA processing window to balance tensile strength and GA performance, possessing ultra-high strength (exceeding 1480 MPa) and excellent ductility. Meeting this need will improve manufacturing reliability, particularly in facilities using induction heating. Although various steels and methods for manufacturing steel have been created and used, it is believed that no one prior to the inventor had ever created or used the invention as described herein. Brief explanation of the drawing
[0011] Although this specification concludes with claims that specifically describe and clearly claim the invention, the invention is to be better understood from the following description of specific examples taken together with the accompanying drawings, in which similar reference numbers identify identical elements. Figure 1 is a schematic graph of the full austenite and quenching and tempering (FA / QT-GI / GA) approach to obtain 20 to 65% martensite and tempered martensite at high temperatures through galvanizing and galvanizing annealing treatments. Figure 2 is a schematic graph of a critical inter-annealing (IA-GI / GA) approach in which there is a critical inter-annealing treatment window between Ac3 and Ac1 to obtain 10 to 25% ferrite, followed by galvanizing and galvannealing heat treatments. Figure 3 is a schematic graph of the critical annealing and quenching and tempering (IA / QT-GI / GA) approach, where there is a critical annealing window and then a quenching and tempering window with galvanizing and galvannealing heat treatments. FIG. 4 is a schematic diagram of a critical annealing window showing an unoptimized composition having a very narrow critical annealing window and an optimized composition having a critical annealing window 2 to 3 times wider. The drawings are not intended to be limiting in any way, and it is understood that various embodiments of the invention may be performed in various other ways, including those not necessarily depicted in the drawings. The accompanying drawings, which are incorporated into and form part of the specification, illustrate various aspects of the invention and serve to explain the principles of the invention together with the description. However, it should be understood that the invention is not limited to the exact arrangements shown. Specific details for implementing the invention
[0012] The following description of specific examples of the present invention should not be used to limit the scope of the invention. Other examples, features, aspects, embodiments, and advantages of the present invention will become apparent to those skilled in the art from the following description, which is one of the best modes considered for carrying out the present invention. As can be seen, the present invention can embody all other distinct and obvious aspects without departing from the invention. Accordingly, the drawings and description should be regarded as illustrative rather than restrictive.
[0013] As explained above, in conventional steelmaking, there was a trade-off between high strength and galvanizing performance (GA performance), with strength being sacrificed to achieve high GA performance. Specific embodiments of this disclosure aim to resolve this trade-off by using a new alloy concept for ultra-high strength steel sheets with a minimum tensile strength of 1480 to 1750 MPa and a new method for manufacturing such ultra-high strength galvanizing (GI) and / or galvanizing (GA) steels. This new alloy concept and manufacturing method widen the GI / GA processing window to achieve a good combination of high strength and GA performance.
[0014] Certain embodiments of this disclosure provide a combination of yield strength, tensile strength, ductility, and formability, offering a wide GI / GA processing window and excellent manufacturing reliability that could not be achieved with conventional steel manufacturing. In some examples, the resulting steel of the composition and method disclosed herein has a tensile strength of 1480 to 1750 MPa, a yield strength of 1050 to 1280 MPa, and a total elongation of 7% or more. In this regard, embodiments of this disclosure relate to ultra-high strength galvanizing and / or galvanizing steel sheets having high tensile and yield strengths and good ductility, formability, and galvanizing performance. In one example, the alloy composition in weight percentage is as follows: C 0.15 to 0.26%, Mn 2.10 to 3.60%, Si 0.05 to 0.85%, Al 0.001 to 0.85%, Cr 0.01 to 0.90%, Mo 0.01 to 0.50%, Ti 0.01 to 0.10%, Nb 0.01 to 0.04%, V 0.01 to 0.30%, B 0.0001 to 0.005%, N less than 0.01%, S less than 0.01%, P less than 0.05%. The remainder is Fe and incidental impurities.
[0015] Three exemplary manufacturing approaches can be used in conjunction with the alloy concept, and these manufacturing approaches include (1) full austenite and quenching and tempering (FA / QT-GI / GA), (2) intercritical annealing (IA-GI / GA), and (3) intercritical annealing, quenching and tempering (IA / QT-GI / GA). When using IA-GI / GA and IA / QT-GI / GA, the steel microstructure consists of 10 to 25% ferrite, 75 to 90% martensite, and 3 to 10% retained austenite in terms of area ratio. When using FA-GI / GA, the steel microstructure consists of 20 to 65% tempered martensite, 35 to 80% new martensite, and 3 to 10% retained austenite in terms of area ratio, which combines high strength and excellent galvanized annealing performance.
[0016] To achieve excellent GA performance in ultra-high strength steel, a sufficient amount of magnetic phases (e.g., ferrite and / or martensite) in the microstructure at high temperatures is required to ensure the GA process. The higher the proportion of magnetic phases, the better the GA performance. However, ferrite is a soft phase, and tempering and over-aging martensite are not hard phases. To achieve ultra-high strength, a higher proportion of hard phases is required. This can be achieved by increasing the strength of the ferrite and over-aging martensite phases. In some embodiments described herein, available strengthening mechanisms include at least one of the following: (A) solution strengthening of Mn, Si, Al, Mo, etc.; (B) precipitation strengthening of vanadium carbide, titanium carbide, and / or niobium carbide; (C) grain refinement strengthening; and / or (D) strain strengthening by tempering rolling and / or stretching.
[0017] In addition to reinforcing all phases, the volume fraction of the softer phase (magnetic phase) is also controlled to optimize ultra-high strength by widening the GA performance and the QT or IA treatment window. In the FA / QT-GI / GA approach, the microstructure is designed with 20 to 65%, preferably 35 to 50%, QT tempered martensite for robust GA performance; 35 to 80%, preferably 65 to 50%, novel martensite for ultra-high strength; and 3 to 10%, preferably 5 to 8%, retained austenite for strain strengthening and excellent ductility. In the IA-GI / GA and IA / QT-GI / GA approaches, the microstructure is designed with 10 to 25%, preferably 13 to 19%, ferrite for robust GA performance; and 75 to 90%, preferably 80 to 75%, martensite for ultra-high strength; For strain strengthening and excellent ductility, it is designed with 3 to 10% residual austenite, preferably 5 to 8%.
[0018] The following paragraph explains at least a few exemplary reasons for the selection of the composition and range of the alloy concept described above. In some cases, the term "approximately" may be used when describing the range or value of a compositional element. In this case, the term "approximately" must have the broadest meaning according to the understanding of a person skilled in the art, or, if the broadest meaning according to the understanding of a person skilled in the art is unknown or inconclusive, it must have + / - 10% of the specified value.
[0019] Carbon: 0.15% or more and 0.26% or less. Carbon is an essential element used to strengthen martensite. If the carbon content is less than 0.15%, the minimum desired tensile strength of 1480 MPa cannot be achieved. If the carbon content is higher than 0.26%, ductility decreases and weldability deteriorates. Additionally, if the carbon content is high, the martensite start (Ms) temperature becomes very low, and the QT window narrows. Preferably, the carbon content is in the range of 0.18 to 0.22%.
[0020] Manganese: 2.10% or more and 3.60% or less. Manganese is a component that strengthens martensite and solid solution strengthens ferrite. It is necessary to ensure a desired amount of hard phase to achieve a tensile strength of 1480 to 1750 MPa. If the manganese content is less than 2.10%, the tensile strength will be less than 1480 MPa. If the manganese content is higher than 3.60%, segregation of Mn may occur, which may have a negative effect on tensile strength. Preferably, the manganese content is in the range of 2.60 to 3.30%.
[0021] Silicon: 0.05% or more and 0.85% or less. Silicon increases strength through solid solution strengthening and also acts as a ferrite stabilizer that raises the Ac3 temperature. Excessive amounts of silicon reduce hot workability. Furthermore, silicon oxide may form on the surface, which can impair coating properties by hot plating. In the IA-GI / GA or IA / QT-GI / GA approach, the addition of silicon content should be optimized by adding aluminum to widen the IA processing window. Preferably, the silicon content is in the range of 0.15 to 0.60%.
[0022] Aluminum: 0.001% or more and 0.80% or less. Aluminum forms AlN to avoid the formation of boron nitride, and it is also a powerful ferrite stabilizer that significantly raises the Ac3 temperature. Excessive amounts of aluminum lead to very high annealing temperatures, causing manufacturability issues. Therefore, the aluminum content is optimized along with the silicon content to widen the IA processing window. Preferably, the aluminum content is in the range of 0.15 to 0.50%, particularly in the IA-GI / GA or IA / QT-GI / GA approaches. Additionally, the total addition of aluminum and silicon is optimized to obtain 3 to 10% retained austenite. Preferably, the total aluminum and silicon content is in the range of 0.6 to 1.2%.
[0023] Chromium and molybdenum: Cr 0.01% or more and 0.90% or less; Mo 0.01% or more and 0.50% or less. Chromium and molybdenum inhibit the formation of ferrite and pearlite when cooled from the annealing temperature and improve hardenability and tensile strength. If the sum of chromium and molybdenum exceeds 0.8%, difficult cold rolling problems may occur.
[0024] Vanadium: 0.01% or more and 0.30% or less. Vanadium is a carbide-forming element. It strengthens ferrite and tempered martensite through precipitation strengthening. Preferably, the vanadium content is in the range of 0.030 to 0.150%.
[0025] Titanium: 0.01% or more and 0.10% or less. Titanium is added to form TiN to protect boron in the solid solution. Additionally, when excess titanium is added together with molybdenum, it forms fine titanium carbides to strengthen ferrite and tempered martensite.
[0026] Niobium: 0.01% or more and 0.04% or less. Niobium can form precipitates and have a grain refinement effect that increases tensile strength.
[0027] Boron: 0.0005% or more and 0.005% or less. Boron can inhibit ferrite formation when cooled from the annealing temperature. Therefore, it helps prevent the tensile strength from dropping below 1480 MPa. In some examples, boron may be 0.0005% or more and 0.003% or less.
[0028] Sulfur: 0.01% or less. Sulfur combines with manganese to form MnS, which is an inclusion that causes cracking and weldability problems.
[0029] Phosphorus: 0.05% or less. Excessive phosphorus causes grain boundary segregation, leading to brittleness.
[0030] The remaining steel composition consists of iron and inevitable impurities generated during melting. Table 1 shows several steel examples and some comparative steels with the compositional composition and weight percentages discussed above.
[0031]
[0032] The following describes a method for manufacturing steel sheets of the compositions described in Table 1 above. In one example, approximately 25 kg of ingots were melted in air to obtain one of the preferred compositions. Then, ingots were formed from the molten material through casting, and the ingots were hot-rolled at 1260°C to produce hot bands with a gauge of 3.0 to 4.0 mm. The hot-rolling finishing temperature was 850 to 900°C, and the coiling temperature was approximately 600°C. Then, the hot bands were annealed and cold-rolled with a reduction of 45 to 65% to produce sheets with a gauge of 1.2 mm to 2.0 mm. Compositions F and G were melted in a mill furnace and continuously cast into approximately 18,000 kg of slabs. The slabs were hot-rolled at 1260°C to produce hot bands with a gauge of 3.0 to 4.0 mm. The hot rolling finishing temperature is 850 to 900°C, and the coiling temperature is approximately 600°C. Then, the hot band is annealed and cold rolled with a 45% reduction to produce a sheet with a gauge of 1.8 mm to 2.0 mm.
[0033] Annealing simulations were performed for each composition similar to the hot-dip galvanizing / galvanealing plant thermal profiles according to FIGS. 1 to 3. Tests performed on steel according to the present invention showed that, in the case of the FA / QT-GI / GA approach, it is possible to produce ultra-high strength steel with a maximum tensile strength of 1480 to 1750 MPa by performing full austenitizing annealing in a temperature range of 840 to 860°C (above Ac3), then quenching in a temperature range of 250 to 375°C, and then performing GI / GA and temper rolling. In the case of the IA-GI / GA or IA / QT-GI / GA approach, ultra-high strength steel with a maximum tensile strength of 1480 to 1750 MPa can be produced by performing critical inter-annealing in a temperature range of 750 to 830°C (between Ac1 and Ac3), then cooling or quenching to a temperature below the galvanizing temperature, and then performing GI / GA and temper rolling. Stretch leveling was simulated in the plant annealing line by performing temper rolling with an elongation of 0.15 to 0.25%.
[0034] yes
[0035] Example 1 - Steel A with FA / QT-GI / GA
[0036] An exemplary steel having a composition of 0.200%C, 2.83%Mn, 0.620%Si, 0.018%Al, 0.130%V, 0.500%Cr, 0.110%Mo, 0.026%Ti, 0.021%Nb, 0.0025%B, 0.012%P, 0.0036%S, and 0.0071%N was melt-rolled, hot-rolled, annealed, and cold-rolled. FA / QT-GI / GA approach annealing simulation was performed according to Fig. 1, with an immersion temperature of 840°C and a quenching temperature in the range of 325 to 375°C. This steel has the following tensile properties as shown in Table 2, with a maximum tensile strength (UTS) of 1480 to 1750 MPa and a total elongation (TEL) of greater than 7.0%. Tensile properties were tested in the longitudinal direction. The microstructure consists of 25 to 65% tempered martensite, 70 to 35% novel martensite, and 3 to 10% retained austenite.
[0037]
[0038] Example 2 - Steel B with FA / QT-GI / GA
[0039] An exemplary steel having a composition of 0.206%C, 3.12%Mn, 0.630%Si, 0.033%Al, 0.150%V, 0.510%Cr, 0.090%Mo, 0.028%Ti, 0.020%Nb, 0.0023%B, 0.011%P, 0.0039%S, and 0.0047%N was hot-rolled, hot-rolled, annealed, and cold-rolled. FA / QT-GI / GA approach annealing simulations were performed according to Fig. 1, with an immersion temperature of 840°C and a quenching temperature in the range of 275 to 375°C. This steel has the following tensile properties as shown in Table 3, with a UTS of 1480 to 1750 MPa and a TEL greater than 7.0%. Tensile properties were tested in the longitudinal direction. The microstructure consists of 25 to 65% tempered martensite, 70 to 35% new martensite, and 3 to 10% retained austenite.
[0040]
[0041] Example 3 - Steel C with FA / QT-GI / GA
[0042] An exemplary steel having a composition of 0.224%C, 3.08%Mn, 0.670%Si, 0.031%Al, 0.140%V, 0.410%Cr, 0.090%Mo, 0.029%Ti, 0.020%Nb, 0.0024%B, 0.013%P, 0.0044%S, and 0.0057%N was melt-rolled, hot-rolled, annealed, and cold-rolled. FA / QT-GI / GA approach annealing simulation was performed according to Fig. 1, with an immersion temperature of 840°C and a quenching temperature in the range of 275 to 375°C. This steel has the following tensile properties as shown in Table 4, with a UTS of 1480 to 1750 MPa and a TEL greater than 7.0%. Tensile properties were tested in the longitudinal direction. The microstructure consists of 25 to 65% tempered martensite, 70 to 35% fresh martensite, and 3 to 10% retained austenite.
[0043]
[0044] Example 4 - Steel B having IA-GI / GA or IA / QT-GI / GA
[0045] An exemplary steel having a composition of 0.206%C, 3.12%Mn, 0.630%Si, 0.033%Al, 0.150%V, 0.510%Cr, 0.090%Mo, 0.028%Ti, 0.020%Nb, 0.0023%B, 0.011%P, 0.0039%S, and 0.0047%N was melt-rolled, hot-rolled, annealed, and cold-rolled. IA-GI / GA or IA / QT-GI / GA approach annealing simulations were performed according to FIGS. 2 and 3, and the critical inter-anenealing immersion temperature is 765 to 800°C. This steel has the following tensile properties as shown in Table 5, with a UTS of 1480 to 1750 MPa and a TEL of greater than 7.0%. Tensile properties were tested in the longitudinal direction. The microstructure consists of 15 to 30% ferrite, 80 to 65% martensite, and 3 to 10% retained austenite.
[0046]
[0047] Example 5 - Steel C with IA-GI / GA or IA / QT-GI / GA
[0048] An exemplary steel having a composition of 0.224%C, 3.08%Mn, 0.670%Si, 0.031%Al, 0.140%V, 0.410%Cr, 0.090%Mo, 0.029%Ti, 0.020%Nb, 0.0024%B, 0.013%P, 0.0044%S, and 0.0057%N was hot-rolled, hot-rolled, annealed, and cold-rolled. IA-GI / GA or IA / QT-GI / GA approach annealing simulations were performed according to FIGS. 2 and 3, and the critical inter-immersion temperature was 765 to 800°C. This steel has the following tensile properties as shown in Table 6, with a UTS of 1480 to 1750 MPa and a TEL greater than 7.0%. Tensile properties were tested in the longitudinal direction. The microstructure consists of 15 to 30% ferrite, 80 to 65% martensite, and 3 to 10% retained austenite.
[0049]
[0050] Example 6 - Steel D with FA / QT-GI / GA
[0051] An exemplary steel having a composition of 0.193%C, 2.77%Mn, 0.510%Si, 0.038%Al, 0.140%V, 0.490%Cr, 0.096%Mo, 0.028%Ti, 0.020%Nb, 0.0020%B, 0.012%P, 0.0046%S, and 0.0060%N was melt-rolled, hot-rolled, annealed, and cold-rolled. FA / QT-GI / GA approach annealing simulations were performed according to Fig. 1, with an immersion temperature of 840°C and a quenching temperature in the range of 345 to 360°C. This steel has the following tensile properties as shown in Table 7, with a UTS of 1480 to 1750 MPa and a TEL of greater than 7.0%. Tensile properties were tested in the longitudinal direction. The microstructure consists of 15 to 30% ferrite, 80 to 65% martensite, and 3 to 10% retained austenite.
[0052]
[0053] Example 7 - Steel E with FA / QT-GI / GA
[0054] An exemplary steel having a composition of 0.204%C, 2.87%Mn, 0.500%Si, 0.150%Al, 0.120%V, 0.540%Cr, 0.098%Mo, 0.031%Ti, 0.021%Nb, 0.0022%B, 0.003%P, 0.0007%S, and 0.0058%N was melt-rolled, hot-rolled, annealed, and cold-rolled. FA / QT-GI / GA approach annealing simulations were performed according to Fig. 1, with an immersion temperature of 840°C and a quenching temperature in the range of 320 to 375°C. As shown in Table 8, the tensile properties of this steel are as follows, with a UTS of 1480 to 1750 MPa and a TEL greater than 7.0%. Tensile properties were tested in the longitudinal direction. The microstructure consists of 15 to 30% ferrite, 80 to 65% martensite, and 3 to 10% retained austenite.
[0055]
[0056] Example 8 - Steel E with IA-GI / GA or IA / QT-GI / GA
[0057] An exemplary steel having a composition of 0.204%C, 2.87%Mn, 0.500%Si, 0.150%Al, 0.120%V, 0.540%Cr, 0.098%Mo, 0.031%Ti, 0.021%Nb, 0.0022%B, 0.003%P, 0.0007%S, and 0.0058%N was hot-rolled, hot-rolled, annealed, and cold-rolled. IA-GI / GA or IA / QT-GI / GA approach annealing simulations were performed according to FIGS. 2 and 3, with critical inter-immersion temperatures ranging from 776 to 788°C. This steel has the following tensile properties as shown in Table 9, with a UTS of 1480 to 1750 MPa and a TEL greater than 7.0%. Tensile properties were tested in the longitudinal direction. The microstructure consists of 15 to 30% ferrite, 80 to 65% martensite, and 3 to 10% retained austenite.
[0058]
[0059] Example 9 - Steel F with FA / QT-GI / GA (Mill Material Simulation)
[0060] An exemplary steel having a composition of 0.195%C, 2.99%Mn, 0.610%Si, 0.040%Al, 0.130%V, 0.460%Cr, 0.100%Mo, 0.034%Ti, 0.024%Nb, 0.0015%B, 0.009%P, 0.0012%S, and 0.0046%N was melted and cast in a mill furnace, and then hot rolled, annealed, and cold rolled. An FA / QT-GI / GA approach annealing simulation was performed according to Fig. 1, with an immersion temperature in the range of 850 to 860°C and a quenching temperature in the range of 340 to 346°C. This steel has the following tensile properties as shown in Table 10, with a UTS of 1480 to 1750 MPa and a TEL greater than 7.0%. Tensile properties were tested transversely. The microstructure consists of 15 to 30% ferrite, 80 to 65% martensite, and 3 to 10% retained austenite.
[0061]
[0062] Example 10 - Steel G with FA / QT-GI / GA (Mill Material Simulation)
[0063] An exemplary steel having a composition of 0.206%C, 3.06%Mn, 0.690%Si, 0.041%Al, 0.140%V, 0.440%Cr, 0.103%Mo, 0.034%Ti, 0.023%Nb, 0.0015%B, 0.008%P, 0.0011%S, and 0.0056%N was melted and cast in a mill furnace, and then hot rolled, annealed, and cold rolled. An FA / QT-GI / GA approach annealing simulation was performed according to Fig. 1, with an immersion temperature in the range of 850 to 860°C and a quenching temperature in the range of 340 to 346°C. This steel has the following tensile properties as shown in Table 11, with a UTS of 1480 to 1750 MPa and a TEL greater than 7.0%. Tensile properties were tested transversely. The microstructure consists of 15 to 30% ferrite, 80 to 65% martensite, and 3 to 10% retained austenite.
[0064]
[0065] Example C1 - Comparison of steel Q with FA / QT-GI / GA
[0066] A comparative steel having a composition of 0.199%C, 2.83%Mn, 0.600%Si, 0.029%Al, 0.003%V, 0.001%Cr, 0.003%Mo, 0.027%Ti, 0.010%Nb, 0.0022%B, 0.012%P, 0.0036%S, and 0.0069%N was melt-rolled, hot-rolled, annealed, and cold-rolled. An FA / QT-GI / GA approach annealing simulation was performed according to Fig. 1, with an immersion temperature of 840°C and a quenching temperature in the range of 250 to 350°C. This comparative steel Q has the following tensile properties as shown in Table C1, with UTS ranging from 990 to 1200 MPa, which is much lower than the UTS of 1480 to 1750 MPa described in Examples 1 to 11. The low tensile properties are attributed to a non-optimal composition, such as a lack of reinforcement with chromium and molybdenum.
[0067] [ Table C1 ]
[0068]
[0069] Example C2 - Comparative steel R with FA / QT-GI / GA
[0070] A comparative steel having a composition of 0.200%C, 2.74%Mn, 0.610%Si, 0.028%Al, 0.003%V, 0.520%Cr, 0.096%Mo, 0.026%Ti, 0.020%Nb, 0.0022%B, 0.012%P, 0.0034%S, and 0.0072%N was melted, hot rolled, annealed, and cold rolled. An FA / QT-GI / GA approach annealing simulation was performed according to Fig. 1, with an immersion temperature of 840℃ and a quenching temperature in the range of 250 to 350℃. This comparative steel R has the following tensile properties as shown in Table C2, with a UTS of 1140 to 1285 MPa, which is much lower than the UTS of 1480 to 1750 MPa described in Examples 1 to 11. The low tensile properties are attributed to a non-optimal composition, such as, for example, a lack of precipitation strengthening of vanadium carbides.
[0071] [ Table C2 ]
[0072]
[0073] It should be understood that one or more of the teachings, expressions, embodiments, examples, etc. described herein may be combined with one or more of the other teachings, expressions, embodiments, examples, etc. described herein. Accordingly, the teachings, expressions, embodiments, examples, etc. described below should not be isolated from one another. After showing and describing various embodiments of the invention, it will be readily apparent to those skilled in the art that various suitable methods can be used to combine the contents of the invention through appropriate modifications without departing from the scope of the invention. Such variations and changes are intended to be included within the scope of the claims.
[0074] After showing and describing various embodiments of the present invention, a person skilled in the art to which the scope of the present invention pertains may further apply the methods and systems described herein without departing from the scope of the present invention. Some of such potential modifications have been mentioned, and other modifications will be apparent to those skilled in the art. For example, the examples, embodiments, geometry, materials, dimensions, ratios, steps, etc. discussed above are illustrative and not essential. Accordingly, the scope of the present invention should be considered in light of the following claims and is understood not to be limited to the details of the structure and operation shown and described in the specification and drawings.
Claims
Claim 1 A steel comprising, by weight percentage, 0.15 to 0.26% C, 2.10 to 3.60% Mn, 0.05 to 0.85% Si, 0.001 to 0.85% Al, 0.01 to 0.90% Cr, 0.01 to 0.50% Mo, 0.01 to 0.10% Ti, 0.01 to 0.04% Nb, 0.01 to 0.30% V, 0.0001 to 0.005% B, less than 0.01% N, less than 0.01% S, less than 0.05% P, and the remainder being Fe and impurities, wherein the microstructure of the steel comprises, based on area percentage, 10 to 25% ferrite, 75 to 90% martensite, and 3 to 10% retained austenite, and the steel has a maximum tensile strength of at least Steel, which is ultra-high strength steel with a strength of 1480 MPa. Claim 2 In paragraph 1, the steel is steel formed into a sheet. Claim 3 delete Claim 4 Steel according to paragraph 1 or 2, wherein the maximum tensile strength is 1750 MPa or less. Claim 5 Steel according to claim 1 or 2, wherein the yield strength is 1050 MPa or more and 1280 MPa or less. Claim 6 Steel according to paragraph 1 or 2, wherein the total elongation is 7% or more. Claim 7 delete Claim 8 In claim 1, the steel, wherein the ferrite is 13 to 19%. Claim 9 Steel according to claim 1 or 8, wherein the martensite is 75 to 80%. Claim 10 Steel according to claim 1 or 8, wherein the residual austenite is 5 to 8%. Claim 11 A steel comprising, by weight percentage, 0.15 to 0.26% C, 2.10 to 3.60% Mn, 0.05 to 0.85% Si, 0.001 to 0.85% Al, 0.01 to 0.90% Cr, 0.01 to 0.50% Mo, 0.01 to 0.10% Ti, 0.01 to 0.04% Nb, 0.01 to 0.30% V, 0.0001 to 0.005% B, less than 0.01% N, less than 0.01% S, less than 0.05% P, and the remainder being Fe and impurities, wherein the microstructure of the steel comprises, based on area percentage, 20 to 65% tempered martensite, 35 to 80% novel martensite, and 3 to 10% retained austenite, and the steel Steel, which is ultra-high strength steel with a maximum tensile strength of at least 1480 MPa. Claim 12 In paragraph 11, steel having 35 to 50% tempered martensite. Claim 13 Steel according to claim 11 or 12, wherein the novel martensite is 50 to 65%. Claim 14 Steel according to claim 11 or 12, wherein the residual austenite is 5 to 8%. Claim 15 In any one of claims 1, 2, and 8, the steel wherein the overall microstructure of the steel comprises ferrite and overaged martensite, and said ferrite and overaged martensite are strengthened by one or more of (a) solid-solution strengthening, (b) precipitation of vanadium carbide and / or titanium-niobium carbide, (c) grain refinement, and (d) strain strengthening or work hardening. Claim 16 In any one of paragraphs 1 or 2, 8, 11, and 12, the steel is configured to be used in a galvanizing process and a galvanizing process. Claim 17 Steel having 0.0001 to 0.003% B in any one of paragraphs 1 or 2, 8, 11, and 12. Claim 18 A method for manufacturing steel, comprising: (a) forming an ingot having a composition comprising, in weight percent, 0.15 to 0.26% C, 2.10 to 3.60% Mn, 0.05 to 0.85% Si, 0.001 to 0.85% Al, 0.01 to 0.90% Cr, 0.01 to 0.50% Mo, 0.01 to 0.10% Ti, 0.01 to 0.04 Nb, 0.01 to 0.30% V, 0.0001 to 0.005% B, less than 0.01% N, less than 0.01% S, less than 0.05% P, and the remainder being Fe and impurities; (b) hot rolling the ingot using a hot band having a gauge of 3.0 to 4.0 mm, wherein the hot rolling A method comprising: (c) a step of hot rolling, which is performed at 1260℃, wherein the finishing temperature is 850 to 900℃ and the coiling temperature is 600℃; (d) a step of annealing the hot band; and (d) a step of cold rolling the annealed hot band to form a sheet having a gauge of 1.2 to 2.0 mm by reducing the gauge. Claim 19 In claim 18, the method wherein the steel is fully annealed in a temperature range of 840 to 860°C, then quenched in a temperature range of 250 to 375°C, then galvanized and galvannealed, and then temper-rolled. Claim 20 In claim 18, the method wherein the steel is annealed at a critical temperature range of 750 to 830°C, then cooled below the galvanizing temperature, then subjected to galvanizing and galvannealing treatment, and then temper rolled. Claim 21 In claim 18, the method wherein the steel is annealed at a critical temperature range of 750 to 830°C, then quenched at a temperature below the galvanizing temperature, then galvanized and galvanized, and then temper-rolled. Claim 22 In paragraph 18, a method having 0.0001 to 0.003% B. Claim 23 In claim 18, a method of cold rolling the annealed hot band to reduce the gauge to form a sheet having a gauge of 1.2 to 1.6 mm.
Citation Information
Patent Citations
High-strength flat steel product and method for producing same
KR1020140024903A
High strength cold-rolled steel sheet and galvanized steel sheet having high hole expansion ratio and manufacturing method thereof
KR1020200036759A